The Influence of Social Media Marketing and Customer Experience on Consumer Purchase Intentions: A Case Study of Mixue Ice Cream & Tea Company - Zhang, Huajia; Kohsuwan, Phanasan (Human Behavior, Development and Society, 2024)
In this study the impact of social media marketing and customer experience was investigated on consumer purchase intentions, using Mixue Ice Cream & Tea as a case study. Data were collected through an online survey of 501 Nanjing, China respondents who had purchased products from Mixue Ice Cream & Tea. Structural equation modeling was used for hypothesis testing. The findings revealed that social media marketing and customer experience significantly and positively influenced purchase intentions, with trust and brand awareness as key mediators. The results underscore the importance of innovative social media strategies and high-quality customer experiences in fostering trust and enhancing brand awareness. Practical implications include recommendations for enhancing social media engagement, customer service, and transparent business practices. Future research should expand geographically, incorporate additional variables, and explore emerging technologies. This study contributes to the literature by offering a comprehensive model of consumer behavior and actionable insights for the ready-to-drink tea industry.